2012
DOI: 10.1055/s-0039-1698934
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of surface roughness and hardness of different glass ionomer cements

Abstract: Objectives:The aim of this study was to evaluate surface roughness and hardness of a nanofiller GIC, a resin-modified GIC, three conventional GICs, and a silver-reinforced GIC.Methods:For each material, 11 spcecimens were prepared and then stored in distilled water at 37 °C for 24 h. The surface roughness of 5 specimens was measured using a surface profilometer before polishing and after polishing with coarse, medium, fine, superfine aluminum oxide abrasive Sof-Lex discs respectively. The hardness of the upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
85
4
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 29 publications
8
85
4
2
Order By: Relevance
“…Also, bioactive glasses and ceramics can interact with bone and dentin in biologi-cal environments like saliva (17). Some studies exhibited the remineralizing effect of bioactive glass materials on dentin and antimicrobial properties (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Also, bioactive glasses and ceramics can interact with bone and dentin in biologi-cal environments like saliva (17). Some studies exhibited the remineralizing effect of bioactive glass materials on dentin and antimicrobial properties (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…[242526] According to this, GC9 should have highest delta value followed by GC2 LC, but in our study, GC2 LC showed highest delta value followed by GC 9 and rest of the sequence was similar as above [Figure 2]. This can be explained by the study of Berzin et al .…”
Section: Discussionmentioning
confidence: 58%
“…The first parameter normally considered when evaluating the finishing of a dental surface is roughness. Clearly, low roughness is desired on all dental surfaces as this minimizes the rate of bacterial adhesion, forming biofilm and initiating plaque and eventually caries . Whereas for single dental material surfaces, the golden standard for evaluation of roughness is the atomic force microscope; for complex systems such as the present three‐materials interface, the large inspection volume required makes it necessary to use the three‐dimensional profilometry developed here.…”
Section: Discussionmentioning
confidence: 99%
“…Reviewing the results in Table and Figures and , it can be seen that the group Rel specimens presented surface roughness equivalent to that of specimens in group Pan, but lower than that of specimens in group NX3. In the literature, some authors have tested the degree of morphological defects in CAD‐CAM crowns after polishing was carried out with different techniques, whereas other authors have evaluated the surface roughness of glass ionomer and resinous cements with profilometer after polishing by means of various techniques. None of these studies included a type of prosthesis similar to the one carried out for this analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation